Electrical injection and detection of spin-polarized currents in topological insulator Bi(2)Te(2)Se - Tian, Jifa (Sci Rep, 2015)
Topological insulators (TIs) are an unusual phase of quantum matter with nontrivial spin-momentum-locked topological surface states (TSS). The electrical detection of spin-momentum-locking of TSS has been lacking till very recently. Many of the results are from samples with significant bulk conduction, such as Bi(2)Se(3), where it can be challenging to separate the surface and bulk contribution to the spin signal. Here, we report spin potentiometric measurements in flakes exfoliated from bulk insulating Bi(2)Te(2)Se crystals, using two outside nonmagnetic contacts for driving a DC spin helical current and a middle ferromagnetic (FM)-Al(2)O(3) contact for detecting spin polarization. The voltage measured by the FM electrode exhibits a hysteretic step-like change when sweeping an in-plane magnetic field between opposite directions along the easy axis of the FM contact. Importantly, the direction of the voltage change can be reversed by reversing the direction of current, and the amplitude of the change as measured by the difference in the detector voltage between opposite FM magnetization increases linearly with increasing current, consistent with the current-induced spin polarization of spin-momentum-locked TSS. Our work directly demonstrates the electrical injection and detection of spin polarization in TI and may enable utilization of TSS for applications in nanoelectronics and spintronics.